Prognostic Factors of Postoperative Mortality in Patients with Complicated Right Colon Cancer - Raul Mihailov; Corina Dima; Bianca Georgiana Constantin; Florentin Dimofte; Mihaela Craescu; Lavinia Moroianu; Laura Iuliana Candussi; Virginia Lutenco; Oana Mariana Mihailov; Valerii Lutenco (Life)
The incidence of right colon cancer presenting in a stage with complications is significant. There are major differences in therapeutic approach between elective colon cancer surgery and emergency surgery. Complications such as hemorrhage, obstruction, and perforation require careful evaluation of prognostic factors, with morbidity and mortality rates being much higher compared to elective colon surgery. We retrospectively analyzed a group of 95 patients admitted in an emergency to the County Emergency Hospital St. Apostol Apostol Andrei Galati with complicated tumors of the right colon—occlusive, perforated, or hemorrhagic. A series of clinical and biological parameters were followed in order to identify the prognostic factors in the occurrence of death. We analyzed the specialized literature, comparing our study with other similar research from the most important databases. The postoperative death rate in patients with complicated right colon cancer was high. Most complications were occlusive, followed by hemorrhagic and perforative.